The use of online testing to assess cognitive differences in healthy individuals at high genetic risk of Alzheimer's disease. (1st February 2022) - Lupton, Michelle K; McAloney, Kerrie; Ceslis, Amelia; Robinson, Gail; Thienel, Renate; Breakspear, Michael; Martin, Nicholas G; ,
Abstract: Background: The PISA study aims to characterise the natural history and symptom progression of Alzheimer's disease (AD) at its prodromal phase. Utilising genetic risk prediction we have identified middle‐aged and older Australians at high risk of dementia. In addition to onsite phenotyping, online surveys and cognitive testing have been used to economically collect information from an Australia‐wide sample. Method: We have utilised our population based sample recruitment pool (N=15, 351) of previous research participants who have been genome wide genotyped. Participants are invited to complete a comprehensive online survey, then complete online cognitive assessments, including Cambridge Brain Sciences (CBS), Cogstate, and an emotion recognition task. Result: Thus far nearly 4, 000 participants have taken part in our online survey, and of these 2055 participants have completed the CBS assessment consisting of twelve subtests assessing memory, reasoning, attention, and planning. Recruitment for CBS and the other platforms is ongoing and participants are being invited to complete follow‐up assessments after two years. At baseline we find significant association of both APOE genotype and polygenetic risk scores (PRS) for AD (omitting the APOE region) in healthy middle aged and elderly individuals with cognitive domains tested using the CBS platform. Conclusion: The utility of online cognitive testing for large scale testing in cohort and epidemiological studies will be discussed. The identification of cognitive changes associated with AD risk and prodromal disease gives important insights into mechanisms of AD development throughout the life span and is an opportunity to investigate prodromal markers to allow selection of individuals for early treatment strategies.